2014
DOI: 10.1073/pnas.1406315111
|View full text |Cite
|
Sign up to set email alerts
|

Large sulfur-isotope anomaly in nonvolcanic sulfate aerosol and its implications for the Archean atmosphere

Abstract: Significance The highest S-isotope anomaly is observed in a nonvolcanic period, and the magnitude of anomaly is similar to the largest volcanic eruptions of the 20th century. S-quadruple isotope data provided the first evidence of how super El Niño Southern Oscillation (ENSO) events (1997–1998) have affected the transport and transformation of aerosols to the stratosphere; thus, record of paleo-ENSO events of this magnitude can be traced with the S-isotopic anomaly. High-resolution and high-precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(93 citation statements)
references
References 46 publications
5
86
1
Order By: Relevance
“…3). Shaheen et al (21) distinguished different sources of modern sulfate aerosols based on concentrations and δ 34 S values of SO 4 in ice-core horizons. The low and intermediate δ 34 S ranges (δ 34 S = 1.4-2.6‰ and +12 ± 1.4‰) have been attributed to combining photoexcitation and photodissociation processes affecting different sulfur sources (mainly SO 2 and OCS) in the stratosphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Shaheen et al (21) distinguished different sources of modern sulfate aerosols based on concentrations and δ 34 S values of SO 4 in ice-core horizons. The low and intermediate δ 34 S ranges (δ 34 S = 1.4-2.6‰ and +12 ± 1.4‰) have been attributed to combining photoexcitation and photodissociation processes affecting different sulfur sources (mainly SO 2 and OCS) in the stratosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The low solubility and long atmospheric lifetime with respect to tropospheric chemistry and photolysis enable a significant fraction of OCS to reach the stratosphere (42), where it photo-dissociates to carbon monoxide and elemental sulfur (S 0 ) on UV irradiation in the 200-to 260-nm range. The sulfur atom is oxidized by different pathways (OH/H 2 O 2 /CO 2 /O 3 /O 2 ) to SO 2 and ultimately sulfate, which is thought to contribute to the stratospheric sulfate aerosol layer (21,43). Laboratory experiments have shown that OCS photolysis at short wavelengths does not produce 33 S-isotope anomaly in oxygen-free conditions but negative Δ 36 S down to −1.5‰ (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[163] In high-resolution sulfur isotope records from polar regions,aconsistent pattern is that D 33 S values change from positive to negative during deposition while D 36 Sv alues changes in reverse fashion (negative to positive). Am ass balance of isotopic anomalies (i.e., average D 33 Sa nd D 36 Sv alues equal to zero) in as ingle stratospheric volcanic event can be hardly reached in observation [117,159,160] because ap ortion of sulfate aerosols formed in the stratosphere may deposit during transport, leading to ah ighly spatially heterogeneous mass independent sulfur isotopic signature in the stratosphere as shown in an early twodimensional model. This temporal evolution of sulfur isotopic anomalies highlights mass independent sulfur isotope effects of SO 2 photolytic reactions and sulfate production and their differential atmospheric behaviors during polar transport (e.g.,different transport speed and deposition lifetime).…”
Section: Present-day Sulfur Isotopic Anomaliesmentioning
confidence: 99%
“…2) thus suggest that the atmospheric signal has been little modified by biological activity after deposition and rather indicates that microbial S cycling, if it was present at all, was not a significant component of the Nuvvuagittuq sedimentary environment (10,44). If a shared biogenic control on the S-MIF record at both the beginning and the end of the Archean Eon is unlikely, recurrent gas inputs in the atmosphere by magmatic activity may be able to produce comparable photochemical pathways at any time in the Archean (45)(46)(47). Such a strong geological control on S-MIF record would then be decoupled from singular events like the emergence of biogenically dominated element cycling or intense bombardments by meteorites.…”
mentioning
confidence: 99%